Dissociation of TNF-alpha cytotoxic and proinflammatory activities by p55 receptor- and p75 receptor-selective TNF-alpha mutants. - Barbara, J A (1994)
Human tumour necrosis factor alpha (TNF-alpha) is a pleiotropic cytokine capable of killing mammalian tumour cells in vitro and in vivo, and of enhancing the proinflammatory activity of leucocytes and endothelium, the latter effects limiting its usage as an antitumour agent in humans. Using TNF-alpha mutants with a selective capacity to bind to the TNF p55 receptor (TNFR55) or to the p75 receptor (TNFR75) we show here that these two major activities of TNF-alpha can be dissociated. The TNFR55-selective mutants (R32W, E146K and R32W-S86T) which bind poorly to TNFR75 displayed similar potency to wild-type TNF in causing cytotoxicity of a human laryngeal carcinoma-derived cell line (HEp-2) and cytostasis in a human leukaemic cell line (U937). However, these TNFR55-selective mutants exhibited lower proinflammatory activity than wild-type TNF. Specifically, TNF-alpha's priming of human neutrophils for superoxide production and antibody-dependent cell-mediated cytotoxicity, platelet-activating factor synthesis and adhesion to endothelium were reduced by up to 170-fold. Activation of human endothelial cell functions represented by human umbilical venular endothelial cell (HUVEC) adhesiveness for neutrophils, E-selectin expression, neutrophil transmigration and IL-8 secretion were also reduced by up to 280-fold. On the other hand, D143F, a TNFR75-selective mutant tested either alone or in combination with TNFR55-selective mutants, did not stimulate these activities despite being able to cause cytokine production in TNFR75-transfected PC60 cells.(ABSTRACT TRUNCATED AT 250 WORDS)